2010
DOI: 10.1074/jbc.m109.080838
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate Receptor mGlu7 Activates Phospholipase C, Translocates Munc-13-1 Protein, and Potentiates Glutamate Release at Cerebrocortical Nerve Terminals

Abstract: At synaptic boutons, metabotropic glutamate receptor 7 (mGlu7 receptor) serves as an autoreceptor, inhibiting glutamate release. In this response, mGlu7 receptor triggers pertussis toxin-sensitive G protein activation, reducing presynaptic Ca 2؉ influx and the subsequent depolarization evoked release. Here we report that receptor coupling to signaling pathways that potentiate release can be seen following prolonged exposure of nerve terminals to the agonist L-(؉)-phosphonobutyrate, L-AP4. This novel mGlu7 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…Synaptosomes were obtained from mouse striata as described previously (41) and used for immunomicroscopy analyses (as detailed later). Glutamate release was assayed in synaptosomal preparations from the P2 fraction with glutamate dehydrogenase, and the fluorescence of NADPH was followed by online fluorimetry (LS-50 luminescence spectrometer; PerkinElmer) (41). Stock solutions of WIN-55,212-2 were prepared in DMSO (final concentration in the assay, 0.1%).…”
Section: Methodsmentioning
confidence: 99%
“…Synaptosomes were obtained from mouse striata as described previously (41) and used for immunomicroscopy analyses (as detailed later). Glutamate release was assayed in synaptosomal preparations from the P2 fraction with glutamate dehydrogenase, and the fluorescence of NADPH was followed by online fluorimetry (LS-50 luminescence spectrometer; PerkinElmer) (41). Stock solutions of WIN-55,212-2 were prepared in DMSO (final concentration in the assay, 0.1%).…”
Section: Methodsmentioning
confidence: 99%
“…Supporting a key role in brain physiology, mice lacking mGlu7 were shown to have deficits in amygdala-dependent fear learning and aversive behavior (10), reduced anxiety-and depression-like behavior (11)(12)(13)(14), and alterations in stress responses, including elevated production of brain-derived neurotrophic factor in the hippocampus (15). At the synaptic level, mGlu7 appears to regulate presynaptic GABA and L-glutamate release, which may contribute to mGlu7's regulating role in emotion-relevant brain circuitry (14,16,17). This role is also supported by findings in mice using siRNA-induced knockdown of mGlu7, inducing changes in innate anxiety, physiological and behavioral stress responses, and fear learning (18).…”
mentioning
confidence: 99%
“…Similar effects of AMN082 on the release of glutamate and GABA have been described in the nucleus accumbens [150] and amygdala [144], although it was suggested that the increase in glutamate observed in these studies may have been secondary to the mGlu7-mediated decrease in GABA. However, a further study demonstrating enhanced release of glutamate from cerebrocortical nerve terminals following prolonged exposure of mGlu7 to L-AP4 does support a facilitatory role for this receptor in excitatory transmission [156]. Together, these data suggest that group III mGlu receptors may regulate the release of glutamate in a bimodal and activity-dependent manner.…”
Section: Role Of Group III Mglu Receptors In Synaptic Transmissionmentioning
confidence: 92%